Quality of Sleep and Related Factors among Imam Khomeini Hospital Staff Nurses - Kamal Salehi; Fatemeh Alhani; Khosro sadegh-Niat; Yousef Mahmoudifar; Narges Rouhi (Iran University of Medical Sciences, 2010)
Background and Aim: Sleep and rest are major needs of human which are included in physiologic needs category of Maslow's hierarchy of needs. Since nurses work on morning, evening and night shifts irregularly, they are exposed to sleep problems. The purpose of this study was to investigate the quality of sleep and related factors among staff nurses working in Imam Khomeni hospital affiliated to Tehran University of Medical Sciences and Health Services.   Material and Method: This study had a descriptive - analytical design in which staff nurses working at Imam Khomeini Hospital lacated in Tehran were studied. The samples consisted of 120 nurses selected by simple random sampling. The instrument for data collection was the Demographic Information Questionnaire and Pittsburgh Sleep Quality Index.   Results: The results showed that %62.5 of nurses had low sleep quality %33.5, low sleep quality and only %4.2 had good sleep quality. When examining relationship between sleep quality and the pattern of working shifts, statistical Chi-square test showed a statistically significant relationship (P<0.05) and staff nurses with irregular working shifts had lower sleep quality.   Conclusion: This study showed that a much percent of nurses suffered from low sleep quality. Also, working shift pattern and the amount of work hours played an important role in quality of sleep in staff nurses.